Индивидуализация обучения иностранных студентов в контексте коммуникативно-когнитивного подхода - Гейченко, Е. И.; Васецкая, Л. И.; Гейченко, Катерина Іванівна; Васецька, Лариса Іванівна (My University, 2015)
In this article the aspects of individualization - the factor of effectivity of foreign language studying by students - non-philologists are considered. The principle of individualization is grounded as the basic principle of the communicative and cognitive method to studying of the foreign language communications. The methodical models of individualization of studying are suggested. The interrelationship of the qualities of the students and the methods of studying are described. It is shown the main principles of individualization and the main components, which create the strategy of the individualization of the studying of the foreigners
Keywords: principles of individualization; variability; openness of training programs; language acquisition strategies; foreigners